Influence of crack widths on corrosion of reinforcing steel bar in fiber reinforced cementitious composites - Mihashi, H.; Ahmed, Shaikh; Kobayakawa, A. (RILEM Publications, 2011)
This paper reports the long term test results on the corrosion durability of reinforcing steel in three series of pre-cracked beams containing ordinary mortar, fiber reinforced cementitious composites (FRCC) containing polyethylene (PE) fibers and hybrid fiber reinforced cementitious composites (HFRCC) containing steel cord (SC)-PE fibers. In each series at least four pre-cracked beams with maximum crack width ranging from 0.1mm to 0.5mm are considered. Durability performances of the specimens are examined through regular monitoring of the corrosion current hence the calculated steel loss, the change of the crack width expanded due to corrosion and the corrosion induced crack through visual inspection. At the end of the corrosion tests, the reinforcing bars in all specimens are exposed to observe the corrosion depth and the actual amount of steel loss. Results show that the HFRCC series exhibited excellent performance compared to mortar and FRCC series.